2005
DOI: 10.1126/science.1117551
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic O 2 Formation Tracked by Time-Resolved X-ray Experiments

Abstract: Plants and cyanobacteria produce atmospheric dioxygen from water, powered by sunlight and catalyzed by a manganese complex in photosystem II. A classic S-cycle model for oxygen evolution involves five states, but only four have been identified. The missing S4 state is particularly important because it is directly involved in dioxygen formation. Now progress comes from an x-ray technique that can monitor redox and structural changes in metal centers in real time with 10-microsecond resolution. We show that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
561
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(631 citation statements)
references
References 29 publications
63
561
0
6
Order By: Relevance
“…[f] Reaction order of the scaled ring with respect to OH − on the NHE scale; the reaction order with respect to H + is the negative value of the reaction order with respect to OH − . [g] Determined by XAS 88, 89. [h] Determined by photothermal beam deflection (PBD) 90, 91…”
Section: Resultsmentioning
confidence: 99%
“…[f] Reaction order of the scaled ring with respect to OH − on the NHE scale; the reaction order with respect to H + is the negative value of the reaction order with respect to OH − . [g] Determined by XAS 88, 89. [h] Determined by photothermal beam deflection (PBD) 90, 91…”
Section: Resultsmentioning
confidence: 99%
“…Another area of contention in this mechanism centers on the nature of the high-valent manganese-oxo active species. Recently, it has been proposed that rather than an Mn(V)-oxo, which has not been spectroscopicaly observed [5,50], the active species in the protein is actually a Mn(IV)-oxyl [35], a spin isomer of the Mn (V)-oxo having O radical character. With the oxyl form, Siegbahn [35] finds a 12.5 kcal/mol barrier for a terminal oxyl/bridging oxo coupling in the coordination sphere of Ca.…”
Section: 23mentioning
confidence: 99%
“…Oxides of metals such as iridium, ruthenium, and manganese, in addition to platinum black, are known to evolve small amounts of oxygen in the presence of strong oxidants such as Ce(IV) or oxone [16,102,103] 5 ] 6+ , also known as ruthenium red, have also been shown to have very high activity for oxygen evolution, especially when stabilized as a heterogeneous system [105][106][107]. As shown in Table 1, complexes such as Ru red have oxygen-evolution characteristics comparable to the more well-defined model systems in solution and these characteristics have been found to be considerably improved upon isolation of the catalyst in polymers such as Nafion [55].…”
Section: Heterogeneous Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interpretations of Mn-XANES data have concluded that the S 1 state consists of two Mn(III) and two Mn(IV) ions and that the S 2 state consists of one Mn(III) and three Mn(IV) ions (for review, see refs 5 and 6). Whether the additional oxidizing equivalent of the S 3 state is localized on a Mn ion (7,8) or on a Mn ligand (9,10) The amino acid residues that ligate the Mn 4 cluster are provided mainly by the D1 polypeptide, one of the core subunits of PSII. This ligation environment was predicted on the basis of spectroscopic analyses of site-directed mutants (for review, see ref 11) and has been largely confirmed by recent X-ray crystallographic studies (12,13).…”
mentioning
confidence: 99%